1993
DOI: 10.1128/jcm.31.3.702-705.1993
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of typing methods for Acinetobacter isolates from hospital outbreaks

Abstract: Four methods, namely, biotyping, cell envelope protein electrophoresis, ribotyping, and comparison of antibiograms, were used for strain identification of Acinetobacter isolates from five outbreaks in hospitals. There was good agreement among the methods for the identification of an index strain, but biotyping and the comparison of antibiograms were the least discriminatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 19 publications
(23 reference statements)
0
49
0
4
Order By: Relevance
“…This epidemiological working definition is less stringent than the definitions of a clone used by microbial geneticists [31][32][33][34][35]. The interest in clones has increased over the past decades, due to the emergence of multiresistant or highly virulent clones of pathogenic bacteria that have become widespread and seem to remain stable for prolonged periods [24][25][26][33][34][35][36][37][38]. Ørskov and Ørskov [31] proposed the following formulation: 'The word clone will be used to denote bacterial cultures isolated independently from different sources, in different locations, and perhaps at different times, but still showing so many identical phenotypic and genotypic traits that the most likely explanation of this identity is a common origin.'…”
Section: E F I N I T I O N S R E G a R D I N G I S O L A T E R E L mentioning
confidence: 99%
See 1 more Smart Citation
“…This epidemiological working definition is less stringent than the definitions of a clone used by microbial geneticists [31][32][33][34][35]. The interest in clones has increased over the past decades, due to the emergence of multiresistant or highly virulent clones of pathogenic bacteria that have become widespread and seem to remain stable for prolonged periods [24][25][26][33][34][35][36][37][38]. Ørskov and Ørskov [31] proposed the following formulation: 'The word clone will be used to denote bacterial cultures isolated independently from different sources, in different locations, and perhaps at different times, but still showing so many identical phenotypic and genotypic traits that the most likely explanation of this identity is a common origin.'…”
Section: E F I N I T I O N S R E G a R D I N G I S O L A T E R E L mentioning
confidence: 99%
“…Unfortunately, new molecular typing methods are often proposed for general use without sufficient prior critical evaluation. For example, they may not have been standardised, a minimal number of isolates may have been used for validation, their agreement with epidemiological data may not have been assessed, or the suitability of a specific method-microbe combination for a specific bacterial taxon may not have been addressed [19][20][21][22][23][24][25][26][27][28]. Finally, basic terminology-including fundamental terms such as 'isolate', 'strain', 'type' or 'clone'-is often used differently by different workers in the field of bacterial epidemiology.…”
Section: Introductionmentioning
confidence: 99%
“…baumannii biotype 9 in their system (16) and in all the published studies where biotyping has been done this biotype dominates, making up 2WO% of all A. baumannii isolates. In addition, DNA group 3 strains may also be misidentified as A. baumannii (9,16). In the second part of this study, all 23 strains from the Acb complex were identified genotypically.…”
Section: Discussionmentioning
confidence: 95%
“…DNA-DNA hybridization studies have shown that there are at least 19 DNA groups (genomic species) within the genus Acinetobacter (7,8,17,38). Strains belonging to some of these groups are so similar that phenotypic differentiation between them is not always possible (12,18). These phenotypically similar but genotypically distinct DNA hybridization groups have been designated the Acinetobacter calcoaceticus-A.…”
mentioning
confidence: 99%
“…This complex currently comprises DNA group 1, A. calcoaceticus sensu stricto Bouvet and Grimont (7); DNA group 2, A. baumannii; unnamed DNA group 3 (7); unnamed DNA group 13 (38); and two more as yet unnamed DNA groups (17). With the exception of DNA group 1, which is regarded as an environmental species, each genomic species within the complex has been linked to nosocomial infections (12,17,26). It is thus essential that typing schemes used for epidemiological studies be able to distinguish between isolates in the A. calcoaceticus-A.…”
mentioning
confidence: 99%